NEW RECORD OF THE GREEN RAT SNAKE Ptyas nigromarginata (Blyth, 1854) (SQUAMATA: COLUBRIDAE) FROM SON LA PROVINCE, VIETNAM - Quang Vinh, Luu; A Phanh, Trang; Van Oanh, Lo (Journal of Forestry Science and Technology, 2019)
Green rat snake Ptyas nigromarginata (Blyth, 1854) was originally described from Northeastern India. The species is known in India, Nepal, Bangladesh, Myanmar, Bhutan, China, Thailand to Vietnam. In Vietnam, the Green rat snake Ptyas nigromarginata is a poorly known species with few records from Lao Cai, Lang Son, Hanoi and Kon Tum provinces. The species is diagnosed based on the following characters: Head elongate, distinct from neck; eyes large with round pupils; a single loreal; eight supralabials, fourth and fifth entering orbit; dorsal scale rows 18(16) - 16(14) - 14, four to six median scales keeled; ventral 190 - 209 cloacal divided; subcaudals 123 - 142, paired. During recent herpetological survey in the karst forest of Van Ho district, Son La province, Vietnam, a male specimen of the Green rat snake Ptyas nigromarginata (Blyth, 1854) was found and this is the first provincial record of the species from Son La province. The specimen of Ptyas nigromarginata from Son La province has 212 ventral scales versus 190 - 209 in the species description of Smith (1943). The specimen was collected at an elevation of 1112 m a.s.l. and it is in the altitudinal range of the species, between 500 and 2300 m. The preferred habitat of the species predominantly consists of temperate forests and montane forest or dense hill evergreen forest. While, the individual in this study is found in the karst forest nearby cultivation area. Further research on population status and threats to the species is urgently required to provide baseline data for conservation measures.